Eine neue Onthophagus-Art aus Israel. 99. Beitrag zur Kenntnis der Scarabaeidae (Coleoptera). - Balthasar, Vladimir (Contributions to Entomology = Beiträge zur Entomologie, 1960)
Onthophagus (s. str.) bytinskii n. sp. from Israel is described and compared with Onthophagus furciceps Marseul. Nomenclatural Actsbytinskii Balthasar, 1960 (Onthophagus (s. str.)), spec. n.